The relationship between sleep and work: A meta-analysis - Litwiller, Brett; Snyder, Lori Anderson; Taylor, William D; Steele, Logan M (Journal of applied psychology, 2017)
Sleep has tremendous importance to organizations because of its relationship with employee performance, safety, health, and attitudes. Moreover, sleep is a malleable behavior that may be improved by individual and organizational changes. Despite the consequential and modifiable nature of sleep, little consensus exists regarding its conceptualization, and how the choice of conceptualization may impact relationships with organizational antecedents and outcomes. To offer a stronger foundation for future theory and research about employee sleep, this study calculated meta-analytic correlations of sleep quality and sleep quantity from 152 primary studies of sleep among workers in organizations. Analyses revealed that both sleep quality and sleep quantity associated negatively with workload and a number of health, attitudinal, and affective outcomes. Despite their conceptual similarity, notable differences existed in sleep quality and sleep quantity in terms of their relationships to many different correlates. Generally, the relationships between sleep quality and the examined correlates were stronger for variables that reflected perceptions. Moderator analyses showed that relationships between sleep quality and quantity may be affected by measurement method and the number of self-report items used, while there is little evidence of the effect of measurement time frame. Findings from this first meta-analytic investigation of the occupational sleep literature have implications for the development of theory about relationships between sleep and work, the measurement of sleep, the identification of organizational correlates of sleep, and the design of interventions intended to improve employee sleep. (PsycINFO Database Record